GsMAPK4, a positive regulator of soybean tolerance to salinity stress - You-wen QIU; Zhe FENG; Ming-ming FU; Xiao-han YUAN; Chao-chao LUO; Yan-bo YU; Yan-zhong FENG; Qi WEI; Feng-lan LI (Journal of Integrative Agriculture, 2019)
Salt stress is one of the major factors affecting plant growth and yield in soybean under saline soil condition. Despite many studies on salinity tolerance of soybean during the past few decades, the detailed signaling pathways and the signaling molecules for salinity tolerance regulation have not been clarified. In this study, a proteomic technology based on two-dimensional gel electrophoresis (2-DE) and mass spectrometry (MS) were used to identify proteins responsible for salinity tolerance in soybean plant. Real-time quantitative PCR (qRT-PCR) and Western blotting (WB) were used to verify the results of 2-DE/MS. Based on the results of 2-DE and MS, we selected glucosyltransferase (GsGT4), 4-coumarate, coenzyme A ligase (Gs4CL1), mitogen-activated protein kinase 4 (GsMAPK4), dehydration responsive element binding protein (GsDREB1), and soybean cold-regulated gene (GsSRC1) in the salinity tolerant soybean variety, and GsMAPK4 for subsequent research. We transformed soybean plants with mitogen-activated-protein kinase 4 (GsMAPK4) and screened the resulting transgenics soybean plants using PCR and WB, which confirmed the expression of GsMAPK4 in transgenic soybean. GsMAPK4-overexpressed transgenic plants showed significantly increased tolerance to salt stress, suggesting that GsMAPK4 played a pivotal role in salinity tolerance. Our research will provide new insights for better understanding the salinity tolerance regulation at molecular level.